2018
DOI: 10.1016/j.ejvs.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Outcomes of Colonic Ischaemia in Abdominal Aortic Aneurysm Repair

Abstract: Post-operative CI after AAA repair is not common but is associated with worse in hospital outcomes and lower long-term survival. EVAR was protective after both rAAA and iAAA repairs. When discussing the treatment of AAA with patients the protective effect of EVAR should be considered. Future studies should validate predictive scores and advance preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…After elective endovascular AAA repair, the incidence of colonic ischemia was reported to be approximately 0.5% to 1.0%, with increased odds of morbidity and mortality. [29][30][31] Interestingly, to the best of our knowledge, no valid association between bleeding, transfusion, and colonic ischemia after complex aortic repair was reported before this study.…”
Section: Discussionmentioning
confidence: 53%
“…After elective endovascular AAA repair, the incidence of colonic ischemia was reported to be approximately 0.5% to 1.0%, with increased odds of morbidity and mortality. [29][30][31] Interestingly, to the best of our knowledge, no valid association between bleeding, transfusion, and colonic ischemia after complex aortic repair was reported before this study.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, diagnosis of CI after aortic surgery requires a high index of suspicion, especially in patients with rAAA. Current literature suggests that EVAR is associated with lower rates of CI compared to OR [4,5]. For example, Italicized entries mean statistically significant results CI, colonic ischaemia In this study, CI was diagnosed in 20 of 35 within the first four postoperative days.…”
Section: Discussionmentioning
confidence: 60%
“…The online version of this article (https://doi.org/10.1007/s00423-020-01964-2) contains supplementary material, which is available to authorized users. endovascular techniques (EVAR) seemed to be protective after repairs of both ruptured and intact AAA [5]. Williamson et al [4] also reported a reduced incidence of CI after EVAR in their meta-analysis compared to open repair (OR).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The colonic resection was adapted to the IC extension, leading to a great majority of subtotal or total colectomies. Previous studies reported high mortality rates for IC developed after ruptured AAA repair surgery [15,16,20,26,40], with some differences related to the type of aortic surgery [14,22,40]. Indeed, a recent systematic review and metaanalysis demonstrated that IC occurs more frequently after open repair (2.1-3.6%) than in EVAR (0.5-1%) in the elective setting [22].…”
Section: Discussionmentioning
confidence: 99%